2019
DOI: 10.1111/joor.12841
|View full text |Cite
|
Sign up to set email alerts
|

The association between mucosal pain and subjective masticatory function in patients with partial removable dental prostheses

Abstract: Background Improvement of masticatory function is critical in prosthetic treatment. Multiple factors are related to patients' perception of chewing ability in denture wearers. However, the associations between such factors and chewing ability have not yet been fully elucidated. Objective To investigate the association between mucosal pain and subjective masticatory function in patients with partial removable dental prostheses (PRDPs). Methods This cross‐sectional study included 333 consecutive patients with PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The FIQ employed in this study has been well validated in partially dentate individuals in a previous study 17 . The FIQ score was also shown to be significantly associated with the number of the remaining tooth, denture‐related mucosal pain and oral health–related quality of life in partially dentate individuals 8,23,24 . These findings indicate the usefulness of FIQ in evaluating subjective chewing ability in this population.…”
Section: Discussionsupporting
confidence: 54%
“…The FIQ employed in this study has been well validated in partially dentate individuals in a previous study 17 . The FIQ score was also shown to be significantly associated with the number of the remaining tooth, denture‐related mucosal pain and oral health–related quality of life in partially dentate individuals 8,23,24 . These findings indicate the usefulness of FIQ in evaluating subjective chewing ability in this population.…”
Section: Discussionsupporting
confidence: 54%
“…Denture sores were another major source of maintenance needs in the present investigation. Studies have shown that interim dentures are associated with increased mucosal pain and, accordingly, with reduced chewing ability [18,19]. An effort should therefore be made to achieve secure and pain-free seating of the denture so that good masticatory function will be ensured.…”
Section: Oral-health Implicationsmentioning
confidence: 99%
“…activation, and proper response of muscle and other connective tissue structures [14][15][16][17][18]. Rehabilitation of masticatory function is one of the main goals of dental treatment, and several previous works have attempted to reveal not only the associated local factors such as tooth loss, periodontitis, decreased masticatory force, temporomandibular disorders, dry mouth, and abnormal occlusal relationships but also related systemic factors including sarcopenia and osteoporosis [9,19].…”
mentioning
confidence: 99%